Brazilian sertanistas: a bridge between two worlds - Romero, Zeus Moreno; Priori, Angelo [UNESP] (Universidade Estadual de Ponta Grossa (UEPG), 2023)
This paper aims to analyze the sertanistas’ historical role in Amazon, specifically Marshal Rondon, Francisco and Apoena Meireles, and also to highlight the two forms of indigenous policy they employed, namely protectionist and integrationist, targeting self-isolated indigenous groups. The bibliographical analysis carried out in this study evidenced that the sertanistas’ work was to bridge the gap between the indigenous and non-indigenous world, in the least traumatic and violent way possible.
Sertanistas brasileiros: uma ponte entre dois mundos
Keywords: Amazon; Integrationist; Rondon, Meireles, Protectionist; Sertanistas